REKRUTMEN DAN PENGEMBANGAN PNS DALAM PERSPEKTIF GOOD GOVERNANCE DI KABUPATEN LOMBOK TENGAH - Agus Agus (KOMUNITAS, 2017)
The purposes of this research are to describe; the condition of civil servants (PNS), the implementation of recruitment and development of civil servants, also problems and policy solutions for good governance practices in the recruitment and development of civil servants in Central Lombok. The result of research, there is surplus (excess) of the number of civil servants who have to occupy the position on Echelon III, those are 4,241 people and echelon II are 73 people. The implication is unhealthy competition to obtain structural positions, which then disturbs the health of bureaucratic organizations. Recruitment of civil servants is guided by Government Regulation (PP) No. 98 of 2000 which constructs six stages of work; planning, announcement, application, screening, appointment of CPNS up to appointment to be civil servant. The position of Regent as the officer of the regional staffing authority gives him authority in the appointment of echelon IV to Echelon II without any sides’ consideration. As the result, practices of civil servant development policy create three conditions; the growth of spoils system practices, the improper use of the work of Baperjakat, and ultimately the practices disturb the independence of Baperjakat work. Good governance practice in civil servant recruitment has practiced aspects of efficiency, transparency and equity, but it has not been seen in the development aspect. Based on the above conditions, this research offers policy solutions to local governments.